2018
DOI: 10.1371/journal.pone.0202167
|View full text |Cite
|
Sign up to set email alerts
|

Efficient feature selection and classification for microarray data

Abstract: Feature selection and classification are the main topics in microarray data analysis. Although many feature selection methods have been proposed and developed in this field, SVM-RFE (Support Vector Machine based on Recursive Feature Elimination) is proved as one of the best feature selection methods, which ranks the features (genes) by training support vector machine classification model and selects key genes combining with recursive feature elimination strategy. The principal drawback of SVM-RFE is the huge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 27 publications
0
51
0
1
Order By: Relevance
“…As such, we applied the Recursive Feature Elimination (RFE) method coupled with Random Forest for measuring variable importance. The RFE technique has been widely applied in healthcare applications due to its efficiency in reducing the complexity (Li, Xie, & Liu, 2018). Furthermore, studies demonstrated that RF-RFE outperformed SVM-RFE in finding small subsets of features with a high discrimination capability and required no parameter tuning to produce competitive results (Granitto, Furlanello, Biasioli & Gasperi, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…As such, we applied the Recursive Feature Elimination (RFE) method coupled with Random Forest for measuring variable importance. The RFE technique has been widely applied in healthcare applications due to its efficiency in reducing the complexity (Li, Xie, & Liu, 2018). Furthermore, studies demonstrated that RF-RFE outperformed SVM-RFE in finding small subsets of features with a high discrimination capability and required no parameter tuning to produce competitive results (Granitto, Furlanello, Biasioli & Gasperi, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the high dimensionality of microarray data frequently means that wrappers and embedded methods cannot be used. This issue inspired an attempt to reduce SVM-RFE time consumption by proposing an improved version of RFE called RFE with variable step size (VSSRFE) [84]. The idea is to use a large step that decreases in size as the number of selected features decreases.…”
Section: Dna Microarray Datamentioning
confidence: 99%
“…Most probably, the classifiers yield worse prognostic performance when trained on such small number of classes [12]. Typically, large dimensionality is one of the significant challenges that faces the interpretation and the analysis of gene expression data measured using microarray technology [13]. In microarray technology, thousands of gene expressions are produced under few conditions' samples.…”
Section: Introductionmentioning
confidence: 99%